La condición fraterna en Antígona de Sófocles (Argos, 2025)
Being conscious that to comprehend a text formally and conceptually is to oscillate between the immediacy and the inaccessibility, G. Steiner holds, in a survey on the projection of Sophocles' Antigone in occidental culture, that we received a deviated significance. In such circumstance, the mentioned author assures that all the elements challenging the comprehension of Antigone are in the first verse of the piece (1991:162). In fact, the initial fraternal exhortation has five words, of which, two, "Oh Ismene", are comprehensible, the rest are objects of voluminous exegesis. Aware of the importance of this verse whose nuclear element is αủτάδελφον, we analyzed its repercussion in the piece. We observed, as well, the lexical field referred to the fraternal condition in the Sophocles' other pieces. After confirming the importance of such kinship in the production of this Athenian tragedian, we noticed that, especially in Antigone, the fraternal condition, articulating the dialectic between public and private space, is privileged beyond any other human condition.
Keywords: Greece; tragedy; Sophocles; Antigone; sister